Expressivism and the value of truth - Sinclair, Neil (Springer, 2012)
This paper is a reply to Michael Lynch's "Truth, Value and Epistemic Expressivism" in Philosophy and Phenomenological Research for 2009. It argues that Lynch's argument against expressivism fails because of an ambiguity in the employed notion of an 'epistemically disengaged standpoint'.